EVALUASI KINERJA SISTEM RBC DI IPAL LAMBUNG MANGKURAT: PENGARUH VARIASI WAKTU TINGGAL TERHADAP EFISIENSI PENURUNAN KADAR BOD - Lia Kurnia Putri (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2018)
Currently, the management of sanitation especially domestic wastewater is very crusial. LambungMangkurat WWTP is applying technology Rotating Biological Contactor (RBC) in the process wastewater.RBC is the secondary processing that uses microorganisms to decompose organic material in wastewater.The purpose of this study to evaluate the performance of RBC in Lambung Mangkurat WWTP and settingvariation of detention time to know how was its effect to efficiency of RBC process to BOD removal. RBCperformance evaluation was conducted by measuring the condition before and after treatment. The settingvariation of detention time by combining pump in RSPS (Raw Sewage Pump Station) and valve in primaryclarifier. Typical of detention time is taken from minimum value 0,7 (hours), middle 1,1 (hours) andmaximum 1,5 (hours). The result of this study, existing condition flow rate is processed range from 530,713m3/day-615,385 m3/day with a detention time between 0,7-4 hours dependent time of the pump. The settingvariation of detention time give effect to efficiency of BOD removal. The biggest detention time of BODremoval is 1,5 (hours).